Angle bracket connections for CLT structures: Experimental characterization and numerical modelling. (10th December 2018) - Pozza, Luca; Saetta, Anna; Savoia, Marco; Talledo, Diego
Highlights: The coupled axial-shear behavior of angle bracket is considered in the formulation. An experimental campaign was specifically designed on CLT panel-AB connections. Monotonic and cyclic behavior of CLT panel-AB connections system are simulated. Degradation phenomena due to cyclic loading are considered. Abstract: This paper presents an enhanced coupled axial-shear model for the monotonic and cyclic behavior of Cross Laminated Timber (CLT) panel – angle bracket connections. The proposed model accounts for the degradation phenomena due to cyclic loading that may affect strength, unloading and re-loading stiffnesses. The main parameters necessary to define the constitutive laws of the model are evaluated by linear regression analyses performed on the data obtained by an extensive experimental campaign specifically designed and carried out at the University of Bologna on CLT panel – angle bracket connections. After the first phase of model calibration, a comparison between numerical and experimental results from both monotonic and cyclic test series are performed to validate the model. These analyses demonstrate the effectiveness of the proposed model in representing the coupled response of angle bracket connections under simultaneous application of axial and shear forces.